THE EFFECT OF TAM ON SATISFACTION OF PPDB REGISTRATION - Anda Yanny; Riza Afni (Institute of Computer Science (IOCS), 2021)
This study uses quantitative descriptive with the number of respondents as many as 35 people, data processing using SPSS 20. The research location is in SMP Negeri 28 Medan. The results obtained indicate that the easier it is to use technology, the higher the satisfaction obtained by PPDB registrants. In terms of the benefits of using PPDB system technology, this does not affect the satisfaction obtained by the registrants. Simultaneously, the ease of using technology and the benefits obtained do not affect the satisfaction of PPDB registrants.